Evolving 'ilm al-akhlaq into a modern discipline of knowledge: prospects and challenges. - Awang Abd Rahman, Amilah (2019)
Al-Akhlaq (Islamic Ethics) is a major dimension of Islam that is responsible for nurturing good and excellent personality. However, its discipline is not recognized in the modern world. This chapter aims at analyzing the challenges as well as prospects of reviving the role of ‘ilm al-akhlaq in meeting the current and future needs of man. The methods applied is critical analysis on available literatures on ethics, both classical and modern. The study came to the finding that this vital field in Islam faces serious challenges. Externally, the secular and atheist lines of thinking claim for their superiority as the most influential solution to the modern man’s problem. Internally, the discourse is typical of traditional approach, and therefore is not only unable to meet the modern needs, but also does not reflect the real meaning of akhlaq of the Qur’an. However, its prospects of being a modern discipline of knowledge and suitable for the modern society are very promising. It is indeed, a theistic, but at the same time, human-centred by taking human experience as its main concern and holistic system of grooming man to the highest level possible. Interestingly, it is also pragmatic as well as dynamic and therefore can sustain its role for all people across generations. ‘Ilm al-akhlaq also is able to train man with modern skills as well as work with modern disciplines including the Social Sciences of all its subordinate disciplines. Hence, developing a full fledge discipline of ‘ilm al-akhlaq is crucially needed so that it feeds the modern needs of man at various levels of concerns: the level of practices, as well as theoretical foundations. Indeed, it is a core area of Islamization of Knowledge which involves interaction between religious knowledge and humanities and Social Sciences.